Transmisi Nilai-Nilai Budaya Pesantren Dalam Strategi Pembelajaran Bahasa Arab Di Indonesia - Muhammad Ilfan Fauzi; Yuli Imawan Imawan; Nur Khozim Muhlis (Jurnal Adab dan Peradaban Islam, 2025)
This study aims to examine the transmission of pesantren cultural values within Arabic language learning strategies in Indonesia. Using a literature review approach and content analysis, the research describes the identification of strategies and mechanisms for transmitting pesantren cultural values. Data are sourced from scholarly articles, books, and relevant previous studies. The findings reveal that Arabic language learning strategies in pesantren are integrated, combining classical and modern approaches, and heavily based on traditional texts such as kitab kuning, with embedded cultural values like simplicity, independence, ethics, and responsibility. Practical-pedagogical implications include strengthening students’ character and creating a spiritual and effective learning environment. The transmission of pesantren cultural values through these strategies fosters students’ linguistic competence, moral character, and high ethical standards. In conclusion, pesantren cultural values serve as a fundamental and inseparable foundation in Arabic language learning strategies, contributing to character development and the identity of Indonesian santri’s scholarly pursuits.